A Bacteriophage for Myxococcus xanthus: Isolation, Characterization and Relation of Infectivity to Host Morphogenesis - Burchard, Robert P. (1966)
Burchard, Robert P. (University of Minnesota, Minneapolis), and M. Dworkin. A bacteriophage for Myxococcus xanthus: isolation, characterization and relation of infectivity to host morphogenesis. J. Bacteriol. 91:1305–1313. 1966.—A bacteriophage (MX-1) infecting Myxococcus xanthus FB(t) has been isolated from cow dung. The bacteriophage particle is approximately 175 mμ long. A tail about 100 mμ in length is encased in a contractile sheath and terminates in a tail plate. The head is polyhedral with a width of about 75 mμ. The nucleic acid of the bacteriophage is deoxyribonucleic acid and has a guanine plus cytosine content of 55.5%. The bacteriophage requires 10(−3)m Ca(++) and 10(−2)m monovalent cation for optimal adsorption. Grown on vegetative cells of M. xanthus FB(t) at 30 C in 2% Casitone medium, the bacteriophage has a latent period of 120 min and a burst size of approximately 100. Host range studies indicate that three strains of M. xanthus including a morphogenetic mutant are sensitive to the bacteriophage, whereas M. fulvus, Cytophaga, Sporocytophaga myxococcoides, and a fourth strain of M. xanthus are not. Of the two cellular forms characteristic of the Myxococcus life cycle, the bacteriophage infect only the vegetative cells; they do not adsorb to microcysts. Ability to adsorb bacteriophage is lost between 65 and 75 min after initiation of the relatively synchronous conversion of vegetative cells to microcysts. The bacteriophage does not adsorb to spheroplasts. After the appearance of visible morphogenesis and before the loss of bacteriophage receptor sites, addition of bacteriophage results in the formation of microcysts which give rise to infective centers only upon germination. The possibility that the infected microcysts are harboring intact bacteriophages has been eliminated.